“I’ll take it with me all my life”: A case study of student teachers’ professional identity development - Akslen, Åse Nylenna; Ohm, Modgun; Hu, Aihua (Nordic Journal of Comparative and International Education (NJCIE), 2023)
Substantial evidence has proved that teacher identity significantly influences teachers’ beliefs and choice of actions in their work, and teacher education contributes to the formation and development process. Based on the findings from analysing student teachers’ pedagogical creeds, this article explores the professional identity development of student teachers who have taken an international course at a Norwegian university. The major data sources are the participants’ pedagogic creeds, supplemented by focus-group interviews with one cohort of students. Findings indicate that identity development is an ongoing process, which can be influenced by different factors. Findings also show that the international course has a positive impact on student teachers’ identity development while writing a pedagogic creed can serve as a dialogical tool for their identity development. This case study provides implications for both international and local teacher education programs in Norway and beyond.